'Maybe what I do know is wrong…': Reframing educator roles and professional development for teaching Indigenous health. Issue 2 (12th October 2022) - Francis‐Cracknell, Alison; Truong, Mandy; Adams, Karen
Abstract: Settler colonisation continues to cause much damage across the globe. It has particularly impacted negatively on Indigenous peoples' health and wellbeing causing great inequity. Health professional education is a critical vehicle to assist in addressing this; however, non‐Indigenous educators often feel unprepared and lack skill in this regard. In this qualitative study, 20 non‐Indigenous nursing, physiotherapy and occupational therapy educators in Australia were interviewed about their experiences and perspectives of teaching Indigenous health. Findings from the inductive thematic analysis suggest educators require skill development to: identify their discomfort in teaching cultural safety; contextualise the sources of this discomfort and; reflect on how this understanding can improve their teaching. Additionally, educators require professional training to become practitioners of cultural humility and to be facilitators and colearners (rather than experts) of the Aboriginal‐led curriculum. Of relevance to this is educator training in how to decentre non‐Indigenous needs and perspectives. Educators can also renew their teaching practices by understanding what a dominant settler paradigm is, identifying if this is problematically present in their teaching and knowing how to remedy this. Crucial to improved cultural safety teaching is institutional support, which includes Indigenous leadership, institutional commitment, relevant policies, and well‐designed professional development.